Corynosoma bullosum Railliet & Henry 1907 - Hernández-Orts, Jesús S.; Kuchta, Roman; Semenas, Liliana; Crespo, Enrique A.; González, Raúl A.; Aznar, Francisco J. (Zenodo, 2019)
Corynosoma bullosum (Linstow, 1892) Railliet & Henry, 1907 Actinopterygii Nemadactylus bergi (Norman) (Perciformes, Cheilodactylidae). SI: mesenteries. SD: cystacanth. L: Chubut Province: northern Patagonian shelf (42º45’– 42º59’S, 61º09’– 62º58’W). R: Hernández-Orts et al. (2019a). Mammalia Physeter macrocephalus Linnaeus (Cetacea, Physeteridae). SI: intestine. SD: unknown stage. L: Chubut Province:Puerto Madryn. R: Berón-Vera et al. (2008), Hernández-Orts et al. (2015). C: vouchers (LAMAMA, accession numbers not provided). Published as part of Hernández-Orts, Jesús S., Kuchta, Roman, Semenas, Liliana, Crespo, Enrique A., González, Raúl A. & Aznar, Francisco J., 2019, An annotated list of the Acanthocephala from Argentina, pp. 1-64 in Zootaxa 4663 (1) on page 29, DOI:10.11646/zootaxa.4663.1.1, http://zenodo.org/record/3772372